PENGEMBANGAN BAHAN AJAR BAHASA INGGRIS BERBASIS KOMPETENSI KERJA UNTUK PROGRAM PELATIHAN VOKASI PERHOTELAN - Andreas Aris Eko Mulyono; Dokman Marulitua Situmorang (Jurnal Teknologi Pendidikan (JTP), 2023)
Abstract: This study aimed to develop and determine the effectiveness of work competency-based English teaching materials for students of hospitality vocational training programs. As an English for Specific Purposes (ESP) program, learning needs analysis (Need Analysis) was a decisive stage in the process of developing teaching materials. In addition to the Need Analysis data, the development of teaching materials also referred to competency units in the Indonesian National Work Competency Standards (SKKNI) for Tourism in the Hotel and Restaurant subsector, the field of English Proficiency and Food and Beverage Services. Teaching materials were developed by adopting the Dick and Carey development model, and studied from two aspects, namely the feasibility aspect of teaching materials and aspects of the effectiveness of the use of teaching materials. Based on the results of the feasibility test, the teaching materials were declared suitable for use in learning activities, while based on the results of the paired t-test, it was found that there were significant differences in the pre-test and post-test values in the experimental class and the experimental class, so that English teaching materials were declared effective in increasing the learners' English competenceÂ